Principle of entrepreneurship (ent530): business model canvas: Popkrispi house / Glenn Achang Henry - Henry, Glenn Achang (2020)
This is a report of a business that I created or established which was asked based on our individual assignment which requires all the students to set up their own business. I have gathered all the information needed such as the business backgrounds, problems faced, price, products, and many more that my business, PopKrispi House have. In this report, I also explain on why I chose the name PopKrispi House as the name of my business, the location, the start-up and also anything that is related to this business’s background. Moreover, I have compiled all the details needed including the registration of the company which is also needed to be in this report. Thus, I have compiled all the important data in this report.